Patterns of Alcohol-Dependence Symptoms Using a Latent Empirical Approach: Associations With Treatment Usage and Other Correlates - Ko, Jean Y. (Rutgers University, 2010)
OBJECTIVE: The aim of this study was to understand the variation in response to alcohol use by identifying classes of alcohol users based on alcohol-dependence symptoms and to compare these classes across demographic characteristics, abuse symptoms, and treatment usage. METHOD: Data from combined 2002-2005 National Survey on Drug Use and Health identified 110,742 past-year alcohol users, age 18 years or older. Latent class analysis defined classes based on observed clustering of alcohol-dependence symptoms based on criteria from the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV). Chi-square statistics were used to test differences in sociodemographic and alcohol-abuse characteristics across classes. Multivariable latent class regressions were used to compare treatment usage across classes. RESULTS: The four-class model had the best overall fit and identified classes that differed quantitatively and qualitatively, with 2.3% of the users in the most-severe class and 83.8% in the least-severe/ not-affected class. These classes differed in a number of demographic characteristics and alcohol-abuse symptoms. All individuals in the most-severe class met DSM-IV criteria for alcohol dependence; 80% of this class had alcohol-abuse symptoms. Twenty-six percent of the moderate and 50% of the moderate-high class met dependence criteria. Approximately 19% of the most-severe class and less than 5% of the moderate and moderate-high class received treatment for alcohol in the past year. CONCLUSIONS: This study demonstrates that meeting dependence criteria only partially captures variations in responses to severity of alcohol problems. Although individuals in the most-severe class were more likely to perceive need and receive treatment, the percentage of individuals receiving treatment was low.